Link Between Academic Performance and Board Exam Results of Civil Engineering Graduates - Ucol, Elvira (Journal of Interdisciplinary Perspectives, 2024)
This study explores the relationship between academic performance and board exam outcomes among Bachelor of Science in Civil Engineering graduates at Nueva Vizcaya State University (NVSU) from 2018 to 2022. The research addresses a critical gap in understanding how specific academic subjects contribute to board exam success, providing insights essential for curriculum improvement and student support. Specifically, the study aims to determine the significance of academic performance in Mathematics, Hydraulics, and Design in predicting board exam results, identifying influential subjects, and developing a predictive model. Using descriptive research design, secondary data on academic grades and board exam ratings were collected from the NVSU Registrar and the Professional Regulation Commission. Correlation and regression analyses revealed that academic performance in Hydraulics had a moderate positive relationship with board exam outcomes, contributing significantly to overall results (r = 0.287, p < 0.05). In contrast, Math and Design exhibited mixed relationships, with some weak negative correlations suggesting the influence of additional factors. Regression analysis indicated that Hydraulics positively predicted board exam results (β = 9.844, p = 0.045), while Math and Design showed less significant or negative contributions. The findings emphasize strengthening the Hydraulics curriculum and aligning Math and Design courses with board exam expectations. With 85.3% of the variance in board exam performance explained by the model (R² = 0.853), the study highlights the substantial impact of academic preparation while recommending targeted interventions and further exploring non-academic factors. This research provides actionable insights for enhancing engineering education and improving licensure exam outcomes.